Design for versatility : the changing face of workspaces for collaborative design - Larsson, Andreas; Törlind, Peter; Bergström, Mattias; Löfstrand, Magnus; Karlsson, Lennart (Luleå tekniska universitet, Innovation och Design, 2005)
In a fiercely competitive business climate, which is increasingly characterized by global alliances, partnerships and outsourcing agreements, companies struggle to decrease the negative impact of geographic distance on development efforts. The role of workspaces for collaborative design is gaining considerable attention, and there is currently an increasing interest in moving from individual tools or technologies to a more inclusive view of collaborative workspaces. This paper reports on the underlying motivation and justification for a new collaborative design studio at Luleå University of Technology, Sweden. The studio provides a rapid-response environment, in which the significance of issues raised through ethnographic observations of engineering work can be evaluated and solutions offered. Godkänd; 2005; 20061121 (petert) ProViking - Development of Functional Products in a Distributed Virtual Environment